Post-operative Right Ventricular Failure After Cardiac Surgery: A Cohort Study - Levy, David; Laghlam, Driss; Estagnasie, Philippe; Brusset, Alain; Squara, Pierre; Nguyen, Lee S. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Right ventricular failure (RVF) after cardiac surgery is an important risk factor for morbidity and mortality. Its diagnosis is challenging, and thus, its incidence and predictors are not well-established. We investigated the incidence, complications, and variables associated with clinically relevant post-operative RVF. Methods: We included all patients who underwent cardiac surgery with cardiopulmonary bypass between 2016 and 2019 in a cardiac surgery center with standardized diagnostic and therapeutic management of RVF. RVF was considered only if clinically relevant: associated with hemodynamic instability requiring catecholamine support and inhaled nitric oxide relayed by sildenafil. Results: Overall, 3,826 patients were included, of whom, 110 (2.9%) developed post-operative RVF. Mortality was not different among patients who developed post-operative RVF, compared with the rest of the cohort (1.8 vs. 0.7%, p = 0.17). Using a composite outcome that combined death, reintubation, stroke, and prolonged intensive care unit stay (more than 14 days) yielded an incidence of 6.6%, and RVF was associated with this composite outcome with an odds ratio of 3.6 (2.2–5.8), p < 0.001. In a multivariable model, pre-operative variables independently associated with post-operative RVF were pre-operative atrial fibrillation (AF) adjusted odds ratio (adjOR) 3.22 [95% confidence interval (95%CI) = 1.94–5.36], p < 0.001, left ventricle ejection fraction below 50% [adjOR = 2.55 (95%CI = 1.52–4.33), p < 0.001], systolic pulmonary artery pressure above 55 mmHg [adjOR = 8.64 (95%CI = 5.27–14.1); p < 0.001], mitral valve surgery [adjOR = 2.17 CI (95%CI = 1.28–3.66), p = 0.004], and tricuspid valve surgery [adjOR = 10.33 (95%CI = 6.14–17.4), p < 0.001]. In patients who developed post-operative RVF requiring treatment, 32 (29.1%) showed RV dysfunction before surgery. Conclusion: In this cohort study, 2.9% of patients developed clinically significant post-operative RVF. Moreover, RVF was associated with severe adverse outcomes, including death, strokes, reintubation, and prolonged intensive care unit stay.